Mobiliser les connaissances et les perceptions des agriculteurs pour reduire les risques sanitaires de l’agriculture irriguee avec des eaux usees. In French. [Harnessing farmers’ knowledge and perceptions for health-risk reduction in wastewater-irrigated agriculture] - Keraita, Bernard N.; Drechsel, Pay; Seidu, R.; Amerasinghe, Priyanie H.; Cofie, Olufunke O.; Konradsen, Flemming (2011)
This chapter addresses the importance of understanding farmers? knowledge and perceptions on health-risk and risk-reduction measures for the development of mutually acceptable risk-management strategies. Drawing on studies from different countries, the chapter shows that it is not realistic to expect high risk awareness. In cases where farmers are aware of health risks, they assess mitigation measures in view of their overall impact on work efficiency and crop yield rather than only the potential health benefits to be gained. The chapter asserts that for on-farm risk-reduction measures to be successful, it is pertinent that farmers? needs and constraints are incorporated into the formulation of recommended practices. This might happen through indigenous processes but can be supported through farm-based participatory approaches where farmers and scientists work together in developing risk reduction measures. An important first step is the identification of mutually accepted problem indicators. Where health benefits for farmers and consumers are not sufficient reasons for the adoption of safer practices, other triggers have to be identified as well as appropriate communication channels for effective outreach.